Sentidos-e-significados sobre práticas de letramento - Silva, Jane Cícero da (2015)
This research aims to analyze and understand the senses-and-meanings (re) built on literacy practices in a Study Group led by a researcher teacher and three students participating through their actions. Therefore, the research on reading sought methodological and theoretical support in the field of Applied Linguistics (LA), based in Moita Lopes (2006). Nestled in the socio-culturalhistorical theory (Vygotsky 1930/1988; 1930/2000; 2007), in language concepts (Bakhtin 2003; 2006) and the literacy issues (Freire 2006; 2014; Soares 200/2007; Kleiman 1995; Rojo 2009; Tfouni 2006). The research methodology used was Research-Action (Thiollent 2007 and Kincholoe 1997), which considers that the transformations of the subjects involved in social phenomena result from interaction and critical reflection. The corpus consists of reflection on reading in three meetings of the Study Group. The analysis was performed based on the linguistic realization of the participants, focusing on the senseand- meanings ascribed to reading. The results show that the sense-andmeanings were (re) constructed in a collaborative process, through negotiation and confrontation to achieve reading comprehension. There was transformation in the students because they felt included in the teaching-learning process in which they had a voice. As for the teacher, her constant strategy changes became evident through her questions